2003
DOI: 10.1183/09031936.03.00026703
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial lung disease in amyopathic dermatomyositis, dermatomyositis and polymyositis

Abstract: This study investigated interstitial pneumonia associated with amyopathic dermatomyositis, dermatomyositis and polymyositis, paying particular attention to muscular and/or cutaneous manifestations and their chronology relative to lung involvement. Patients included four males and 13 females, aged 51.7±10.8 yrs, who had surgical lung biopsy.Diagnoses included dermatomyositis (10 patients), polymyositis (four patients) and amyopathic dermatomyositis (three patients). Solitary respiratory manifestations preceded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
181
2
22

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 240 publications
(211 citation statements)
references
References 28 publications
6
181
2
22
Order By: Relevance
“…Regarding the anti-Jo-1 antibody, only one patient with chronic ILD-ADM had this antibody among the present ILD-ADM study. To date, several studies have reported a low incidence of anti-Jo-1 antibody in ILD-ADM patients [11][12][13][17][18][19]. The current results were consistent with those studies.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Regarding the anti-Jo-1 antibody, only one patient with chronic ILD-ADM had this antibody among the present ILD-ADM study. To date, several studies have reported a low incidence of anti-Jo-1 antibody in ILD-ADM patients [11][12][13][17][18][19]. The current results were consistent with those studies.…”
Section: Discussionsupporting
confidence: 83%
“…These data suggest that chronic ILD is unlikely to pre-exist in the study patients with acute/subacute ILD. Taken together, these results may account for the contradictory data previously reported in the prognosis of ILD-ADM. Namely, the fatal progressive ILD-ADM described is likely to correspond to the acute/subacute ILD-ADM in the present study, while the ILD-ADM with a favourable prognosis reported by COTTIN et al [13] may be equivalent to chronic ILD-ADM. Although ethnic differences may affect the clinical manifestations of ILD-ADM, it should be noted that ILD-ADM has these two different forms.…”
Section: Discussioncontrasting
confidence: 39%
See 3 more Smart Citations